P386 Clinical presentation, management, and evolution of lymphomas in patients with Inflammatory Bowel Disease: an ENEIDA registry study. (30th January 2023) - Guerra Marina, I; Bujanda, L; Mañosa, M; Pérez-Martínez, I; Casanova, M J; de la Peña, L; de Benito, M; Rivero, M; Varela, P; Bernal, L; Franco, A C; Ber, Y; et al.
Abstract: Background: An increased risk of lymphoma has been described in patients with Inflammatory Bowel Disease (IBD). The aims of our study were to determine the clinical presentation of lymphoma, previous exposure to immunosuppressive and biologic therapies, and the management and evolution of lymphomas in patients with IBD. Methods: IBD patients with diagnosis of lymphoma from October 2006 to June 2021 were identified from the prospectively maintained ENEIDA registry of the Spanish Working Group on Crohn's Disease and Ulcerative Colitis (GETECCU). Investigators at each participating centre provided additional information on lymphomas. Results: We identified 52 patients with lymphoma in 18 centres following 21, 740 patients with IBD (2.4 cases of lymphoma/1, 000 patients with IBD; 95% CI 1.8-3.1). 35 were men (67%) and 27 (52%) had Ulcerative Colitis. Non-Hodgkin lymphoma was the most common lymphoma (65%). The median age at diagnosis of lymphoma was 59 years old (IQR 48-67). 31 patients (60%) received thiopurines, and 20 (38%) an anti-TNF drug (one of them had not received thiopurines) before lymphoma diagnosis. Age at diagnosis of lymphoma was lower in those patients treated with thiopurines (53 ± 17 years old) and anti-TNF drugs (47 ± 17 years old) than in those patients not treated with thiopurines nor anti-TNF drugs before the diagnosis of lymphoma (63 ± 12 years old; p<0.05 for both). The most common signs were adenopathy or mass (38%). Most of patients were treated with chemotherapy (77%). Median follow-up after lymphoma diagnosis was of 57 months (IQR 39-102 months). After diagnosis of lymphoma, IBD treatment was changed in 30 patients (58%), and 3 (5.8%) patients received thiopurines and 8 (15%) biologics during follow-up. Those patients who required to be treated with immunosuppressants or biologic therapies after lymphoma diagnosis had an IBD flare more frequently than those patients without these treatments (75% vs. 20%; p=0.01). 5 cases had relapse of lymphoma (incidence of 1.7 cases/100 patient-years; 95% CI 0.7-4.0), with a median of 38 months (IQR 23-84 months) from the diagnosis. 9 patients (17%) died after 19 months (IQR 0-48 months). Relapse and mortality were not related with the type of IBD or lymphoma, sex, smoking habit nor with the use and duration of thiopurines or biologic therapies. Conclusion: Most IBD patients with lymphoma had been treated with thiopurines and/or anti-TNF agents before lymphoma diagnosis, and these patients were younger at diagnosis of lymphoma than those not treated with these drugs. IBD treatment was usually changed after a diagnosis of lymphoma. Relapse and mortality of lymphoma were not related to the use and duration of thiopurines or biologic therapies.